FROM WAHABI PESANTREN TO PROGRESSIVE ISLAM: Socio-Intelectual Legacy of Moeslim Abdurrahman (1948-2012) - Najib, Muhammad Ainun; Fata, Ahmad Khoirul (UIN Sumatera Utara, 2025)
Moeslim Abdurrahman is one of the well-known Indonesian Islamic intellectuals who introduced the idea of transformative Islam—an approach that seeks to position Islam within the context of defending marginalized groups and promoting equitable social change. Moeslim views Islam not only as a religion but also as a tool for social critique and a means of advocating for marginalized communities. Based on Edward W. Said’s concept of traveling theory, transformative islamic thought represents the culmination of Moeslim’s intellectual journey, shaped by his Wahhabi educational background and his PhD studies at the University of Illinois at Urbana-Champaign, United States. The idea of transformative Islam has faced various criticisms, with some arguing that it lacks contextual relevance within indonesian Islam. Nevertheless, transformative Islamic thought has firmly established itself within Indonesia’s Islamic discourse. Moreover, Moeslim served as an intellectual mentor for JIMM, which was founded in 2003. His contributions positioned him as one of the key intellectuals striving to revitalize muhammadiyah's intellectualism, which had been experiencing stagnation in the development of Islamic thought. Alongside figures such as Ahmad Syafii Maarif and M. Amin Abdullah, Moeslim played a significant role in this intellectual movement.